The cry of the cross for the Filipino people - Federogao, Nelson F. (Quezon City : St. Andrew's Theological Seminary, 1988)
The research started with the different views of the cross as a background that would introduce us to the main concentration of this paper. These will cover the understanding of the cross years back before Jesus started his earthly ministry. This will also include the teachings of the New Testament Christians about the cross and as interpreted by the Filipinos in their Christian living
A degree paper presented to the faculty in partial fulfillment for Bachelor in Theology
Thesis (B.Th. )-- St. Andrew's Theological Seminary